Investigation on a new process chain of deposition or friction welding and subsequent hot forging. Issue 9 (14th September 2013) - Frischkorn, C.; Huskic, A.; Hermsdorf, J.; Barroi, A.; Kaierle, S.; Behrens, B.‐A.; Overmeyer, L.
Abstract According to the state of the art most current forging parts and technical components are made of mono‐materials. Nevertheless, parts consisting of only one material increasingly reach their specific material and constructive limits in the established production processes. Through use of previously joined raw parts consisting of different materials, it is possible to produce application‐optimized hybrid parts. This paper describes the production chain of hybrid parts produced by combining two different joining processes with subsequent hot compression tests. The joining of various materials is realized by a deposition welding with a laser‐stabilized gas‐metal‐arc deposition welding (LGD) process and a conventional friction welding process. Subsequently, the hybrid samples are compressed under varying forming parameters such as temperature and deformation degrees. In order to characterize the joining zone, metallurgical investigations are carried out.